NEGARA REPUBLIK INDONESIA DENGAN KARYA TAFSIRNYA: Al-Qur’an dan Tafsirnya Kementerian Agama RI - Melly Nur Rahmawati (TAFAKKUR : Jurnal Ilmu Al-Qur'an dan Tafsir, 2023)
Most of the Indonesian Muslim community, such as educators, students, and university students, do not know that Indonesia has an original tafsir work coordinated by the Ministry of Religious Affairs. It seems that the original tafsir by the Ministry of Religious Affairs is not popular with the people of Indonesia. On YouTube channel ‘Rumah Fiqih’ it was conveyed directly by ustadz Ahmad Sarwat, Lc., MA. that the Ministry of Religion's tafsir is not the original title, but the Qur’an and its Tafsir. This tafsir is not available for free sale in bookstores or markets, so only certain people can have this Ministry of Religious Affairs tafsir. The research method uses qualitative descriptive, library research, the data collection method uses primary and secondary data. Al-Qur'an and Tafsirnya by the Ministry of Religion, there are two versions of prints, namely Ijmali and Tahlili interpretations, what attracts the author's attention is the long process of preparing this interpretation, one of the interesting things among several works of interpretation from the Ministry of Religion is that the Al-Qur'an and Tafsirnya use the tahlili method. Actually, this tafsir can be owned by anyone, through submission of a request letter, and can be downloaded through the Pustaka Lajnah website in soft copy form. Thus, the Muslim community should already know the existence and popularity of the Qur'an and its Tafsir or what we often call the tafsir of the Ministry of Religious Affairs, because it turns out that although we are difficult to get this tafsir in its physical form, we can have it in another version.